Fenntarthatóság – értékmódszertan - Keszi-Szeremlei, Andrea; Nádasdi, Ferenc (Dunakavics, 2026)
It is still unclear what technological developments the 21st century will bring to humanity, but it is certain that great progress has been made in the field of artificial intelligence. This is none other than the creation of large language models (LLM) and, as a result, the mass emergence of generative AI applications. The aim of this study is to present the areas of AI use among students at the University of Dunaújváros based on the results of a questionnaire survey. The study also covers the opinions of the respondents regarding the inclusion of artificial intelligence applications in the curriculum. A summary evaluation of the results is presented at the end of the paper.